The experience of an extension course in resigning trends in environmental education of muni-cipal public agents - Rezende da Silva Bezerra , Monalisa; Martins de Carvalho , Raphaela; da Cunha Teixeira, Marcos; de Almeida, Renato; Agrizzi, Ana Paula; de Alcântara Tristão, Anna Cláudia Aparecida; Santos Silva , Elzeni (Guará Journal, 2025)
The  objective  was  to  analyze  the  conceptions  of  the  envi-ronment and the political-ideological tendencies of environ-mental education of public agents from 12 municipalities in the  north  of  the  state  of  Espírito  Santo,  participants  of  the  extension  course  “Environmental  education  and  public  po-licies”. When participating, participants filled out a form in which  they  had  to  indicate  which  topics  they  considered  to  be  related  to  the  environment  and  answered  the  following  questions:  (1)  What  is  the  environment?  (2)  How  do  you  de-fine  environmental  education?  The  results  indicate  a  pre-dominance  of  the  conservative  tendency  of  public  agents.  At  the  end,  the  main  changes  promoted  by  the  course  were  evaluated  through  a  questionnaire  and  content  analysis.  The  results  revealed  openings  for  reorienting  conceptions  and trends.
Keywords: Environmental education; Public policy; Environment management; Environment